To rewrite the equation \( \frac{6}{x} - 2 = 3 \) as two equations joined by "and," we first isolate \( \frac{6}{x} \).
Starting with the original equation: \[ \frac{6}{x} - 2 = 3 \]
We add 2 to both sides: \[ \frac{6}{x} = 5 \]
Now we can express this as two separate equations. The first equation represents the equation we derived: \[ \frac{6}{x} = 5 \]
The second part comes from recognizing that the variable \( x \) cannot be zero (since division by zero is undefined): \[ x \neq 0 \]
So, we can rewrite the original equation as: \[ \frac{6}{x} = 5 \quad \text{and} \quad x \neq 0 \]